Pengembangan Kawasan Wisata Pantai Laguna Melalui Peningkatan Kapasitas Mitra - Akmal Abdullah; Rusli Rusli; Ikbal Syukroni; Rudi Latief; Sulkifli Sulkifli (Yayasan Literasi Sains Indonesia, 2023)
The attractiveness of a tourist area is a driving force for a tourism place, therefore the tourist attraction is the main driver that encourages tourists to visit a tourist spot. The method used in this service is the method of transferring knowledge and skills through a participatory approach. The forms of activities provided to partners are training, counseling and mentoring. The stages of the activity begin with observation, namely interviews with relevant government and stakeholders. The activity continued with the socialization of the PIPK program and holding a Forum Group Discussion (FGD) to find out the conditions that are currently happening at the service location, whether in the form of obstacles, threats, constraints or potentials that exist and are feasible to develop. The next stage is formulating alternative policy programs taken, offering the right solution in overcoming problems from partners. The stages of implementation through training and counseling and providing assistance. The results of this community service activity can be seen in each of the Pokdarwis Bahari partners, namely 1 (one) design of a tourism site plan, Availability of adequate facilities, 1 ( one) tourism management structure, 1 (one) online-based promotional media and for lagoon KUB partners, 1 (one) design of fishery product processing equipment as well as diversification of various processed fishery products that are ready to be marketed.